Ethics consultation and empathy. Finding the balance in clinical settings - Frewer, Andreas; Bruns, Florian (HEC Forum, 2011)
There is no doubt that emotions have an important effect on practices of moral reasoning such as clinical ethics consultation. Empathy is not only a basic human emotion but also an important and learnable skill for health care professionals. A basic amount of empathy is essential both in patient care and in clinical ethics consultation. This article debates the ''adequate dose'' of empathy in ethics consultations in clinical settings and tries to identify possible situations within the process of consultation in which this crucial feeling is at risk. © Springer Science+Business Media B.V. 2011.
CRIS-Team Scopus Importer:2025-03-13
Keywords: Clinical Ethics Committee; Clinical Ethics Consultation; Emotions; Empathy